Characterization of the clear-PEM breast imaging scanner performance - E. Albuquerque (2009)
We present results on the characterization of the Clear-PEM breast imaging scanner. Clear-PEM is a dual-head Positron Emission Mammography scanner using APD-based detector modules that are capable of measuring depth-of-interaction (DOI) with a resolution of 2 mm in LYSO:Ce crystals. The full system comprises 192 detector modules in a total of 6144 LYSO:Ce crystals and 384 32-pixel APD arrays readout by ASICs with 192 input channels, which represents an unprecedented level of integration in APD-based PET systems. The system includes Frontend and Data Acquisition electronics and a robotic gantry for detector placement and rotation. The software implements calibration (energy, time and DOI), normalization and image reconstruction algorithms. In this work, the scanner main technical characteristics, calibration strategies and the spectrometric performance in a clinical environment are presented. Images obtained with point sources and extended uniform sources are also presented. The first commissioning results show 99.7% active channels. After calibration, the dispersion of the channels absolute gain is 15.3%, which demonstrate that despite the large number of channels the system is rather uniform. The mean energy resolution at 511 keV is 15.9% for all channels, and the mean DOI constant is 5.9%/mm, which is consistent with a 2 mm DOI resolution, or better. The coincidence time resolution at 511 keV, for a energy window between 400 and 600 keV, is 5.2 ns FWHM. The image resolution measured with point sources was found to be of the order of 1.3 mm FWHM. The DOI capability was found to have a strong impact on the image sharpness. Images of extended uniform (68)Ge sources, corrected for sensitivity and for the artifacts due detector dead spaces, have good uniformity. First clinical breast images are presented.